Telemedical IoT based technology for emergency health-care - Prasad, M. S. R.; Lingampalli, Amrutha; C. Verapalle, Kushal Kumar; N. Malraju, Eshwar (International Journal of Engineering and Technology, 2017)
While it is possible to save potential victims during emergencies situations (such as cardiac arrests) using the required healthcare infrastructure around, the greatest challenge lies in setting up of the same. People are not always present at places with readily access to qualified doctors. As a result, there should be a provision to remain in touch with a specialist medical practitioner. This paper presents the methodology of medical content management through internet of things. Transmitting sensory data of the victims to any hospital on time can help save numerous lives across the planet. This mode of human-machine interaction constitutes telemedicine. By embracing information technology and telecommunication, telemedicine provides remote emergency healthcare services outside the regular medical establishments. These systems generate and process an increasing amount of sensory data. It supports real-time processing with the help of a content management system that averts impending life-threatening dangers. By utilizing suitable sensory data inputs, medical practitioners can analyze and convey the appropriate measures to be taken to save the victim. The underlying methodology is extended to various scenarios such as aircrafts, high-buildings and remote villages. Finally, potential for future improvement and the challenges that are currently faced are presented in this paper.